Conflict management and age in service professions. Issue 3 (11th July 2016) - Beitler, Lena Aline; Machowski, Sabine; Johnson, Sheena; Zapf, Dieter
Abstract : Purpose: The purpose of this paper was to examine age differences in conflict management strategy use, effectiveness and in exposure to customer stressors in service interactions. Design/methodology/approach: Moderated regression and mediation analyses were conducted to test hypotheses in a sample of 444 German service employees from different service branches with frequent customer contact. Findings: Results revealed that older service employees experienced fewer customer stressors. Customer stressors mediated the negative relationship between age and burnout. Age was associated with use of passive avoidant (avoiding) and active constructive (problem solving) conflict management strategies. Furthermore, older employees used those strategies more effectively. Especially when avoiding conflicts, older employees reported more professional efficacy than younger colleagues. In contrast, younger employees benefited considerably less from strategy use and reported higher levels of burnout in general. Thus, results suggest older employees' effective conflict management and their positive perception of customer stressors contribute to lower levels of burnout. Practical implications: Results speak against a general deficit model for older workers as they show specific strengths of older employees in social conflicts. Their expertise in dealing with negative social interactions represents an important resource for organizations and training interventions, such as mentoring programs. Originality/value: This study is one of the first to examine age-related conflict management skills with regard to customer conflicts, employee health and effectiveness of strategy use. It replicates existing findings on age and conflict management and extends them in several ways thereby ruling out alternative explanations for age effects.